Characterization of agar from Gracilaria tikvahiae cultivated for nutrient bioextraction in open water farms. (April 2019) - Rocha, Cristina M.R.; Sousa, Ana M.M.; Kim, Jang K.; Magalhães, Júlia M.C.S.; Yarish, Charles; Gonçalves, Maria do Pilar
Abstract: Gracilaria tikvahiae, an endemic western North Atlantic red alga, was cultivated for nutrient bioextraction in urbanized estuarine waters in Long Island Sound and the Bronx River Estuary, USA. This study assesses the feasibility of an integrated approach of using G. tikvahiae produced in this bioextraction system as sustainable biomass source for agar production. Agars were extracted after alkaline pre-treatment and characterized in terms of gelling strength, chemical composition, chemical structure and gel structure. Results indicated that this seaweed performed similar to other cultivated Gracilaria in terms of extraction yield and gelling strength of the agar. Differences between sites were not significant in terms of agar gel strength, though yield was higher at Long Island Sound. The extracted agars were sulfated, methylated and with no detectable pyruvate substituents. It is possible to use an integrated strategy of nutrient bioextraction in urbanized estuarine waters and agar exploitation with G. tikvahiae . Graphical abstract: Highlights: Agar was successfully extracted from G. tikvahiae used in the nutrient bioextraction systems in urbanized coastal waters. Extracted agar performance was similar to other Gracilaria agars. There were no significant differences in the gelling strength between the two cultivation sites. NMR profile and gel structure of the extracted agars was analyzed.